Reactivity of anodically-generated methoxystilbene cation radicals: The effect of ortho’-substitution / Chong Kam Weng - Chong , Kam Weng (2019)
A systematic study was undertaken to determine the influence of ortho-substituted nucleophilic (OH, NH2, CH2OH, CH2NHR, CO2H, CH=CH2) and non-nucleophilic (OMe, OAc, CN, NO2, CF3, CO2Me, CONH2, CHO) groups on the reactivity of anodically generated 4-methoxy- and 3,4-dimethoxystilbene cation radicals. The results showed that when ortho-substituted nucleophilic groups such as OH or NHR are directly attached to the aromatic ring, both direct and crossover intramolecular cation-nucleophile reactions occur to give bisbenzofurans/bisindoles or fused bisbenzopyrans/bisquinolines, respectively. When the ortho'-substituted side chains have been extended to include an intervening CH2 group (CH2OH, CH2NHR), only direct intramolecular cation-nucleophile reactions occur to give bisbenzopyrans or bisisoquinolines. Crossover products (previously obtained when the ortho substituents were OH and NH2) such as the fused benzoxepanes/fused benzoazepanes were not formed. When the ortho substituents are CO2H and vinyl groups, direct intramolecular cation-nucleophile reaction occur to give the corresponding bis--lactones and bisdihydronaphthalene, respectively. An unusual doubly-bridged, dibenzofused cyclononane derivative is also obtained in the oxidation of the ortho-vinyl-substituted stilbene. When the ortho substituents are non-nucleophilic groups such as OMe, OAc, CN, NO2, CF3, or CO2Me, the products are the tetraaryltetrahydrofurans and dehydrotetralin derivatives. In the case of an ortho-amide substituent, the major products are the tetraaryltetrahydrofurans, accompanied by a minor product incorporating an isocoumarin moiety. When the ortho substituent is a formyl group, the products include fused indanylnaphthalenes, indanylbenzopyran aldehydes, and indenyl benzaldehyde. Where an additional 3-methoxy substituent is present, additional products are formed as a result of competing aromatic substitution/Friedel Crafts reactions. Mechanistic rationalization for the formation of the various products is presented and discussed.